Analysis of Self Medication Practice in the Area of Health Professionals who work in the Medical School of UNIPLAC in Lages- SC (Research, Society and Development, 2020)
The study aimed to investigate the practice of self-medication among professionals working in the medical school of the University of Santa Catarina Plateau (UNIPLAC), in the city of Lages, SC. Self-medication is the practice of using drugs without prescription and / or supervision of medical professionals. Despite erroneous and dangerous, it is quite common and increasingly frequent in the academic and social environment. The survey was conducted by applying 42 questionnaires to collect sociodemographic data of each subject, as well as information about the practice of self-medication for the same by accepting and signing the informed consent (Informed Consent and Informed). Where 76.19% of the participants were female; 92.86% had average family income exceeding 4 minimum wages; 90, 48% reported practicing self-medication and of these more than 40% of frequent form. Another worrying statistic refers to the knowledge of bull of drugs, where almost a third of the participants were unaware of bull and consequently the possible side effects and adverse reactions of the same. Based on the analysis of the results and the literature review, it appears that the lack of more stringent legislation in the control of dispensing drugs, a fact that currently only occurs with some drug classes, coupled with the frequent presence of drug without the advice request an appropriate clinical examination, are the main contributing factors in order to feed the culture of self-medication.